The Indirect Impact of Busy Directors on the Relationship of Family Structure and Cash Flow Sensitivity of Cash (Empirical Research in Indonesia’s Manufacturing Sector 2013-2017) - Santoso, Wahyu; Utama, Cynthia Afriani (Universitas Muhammadiyah Yogyakarta, 2021)
Research aims: This research aimed to determine the impact of family structure on the cash flow sensitivity of cash (CFSC) in the manufacturing sector. It also investigates the indirect impact of busy directors as a moderating effect.Design/Methodology/Approach: Based on a sample of Indonesia’s manufacturing companies from 2013 to 2017, the researcher uses GLS regression models on this panel data calculated with robustness fit test at the firm’s level.Research findings: It indicated that family structure has a impact positively on cash flow sensitivity of cash and statistically significant. Meanwhile, the indirect impact of busy directors found to have a impact negatively and weakened on the relationship of family structure and CFSC, it also indiciated that quality of busy directors is an tool of corporate governance that is effectively to monitor of every family firm’s decisions.Theoretical contribution: This article enriches previous literature by justifying the impact of busy directors on the relation between every each of family’s firm decision and CFSC. Furthermore, it showed us a metric for agency problems that is the sensitivity of cash to corporate cash flows.Implication policy: Based on POJK regulations, the context of busy directors in this research refers to the roles and duties of the Board of Commissioners (BOC) which concurrently hold positions for other public companies.Research Limitation/Implication: The implications suggest that almost most of Indonesian family corporation are tend to expropriate minority by extracting rents through coporate cash flow sensitivity of cash behavior.